2019
DOI: 10.1002/ece3.5699
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome responses during virulence adaptation by a phloem‐feeding insect to resistant near‐isogenic rice lines

Abstract: The microbiomes of phloem‐feeding insects include functional bacteria and yeasts essential for herbivore survival and development. Changes in microbiome composition are implicated in virulence adaptation by herbivores to host plant species or host populations (including crop varieties). We examined patterns in adaptation by the green leafhopper, Nephotettix virescens, to near‐isogenic rice lines (NILs) with one or two resistance genes and the recurrent parent T65, without resistance genes. Only the line with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…The adaptation capability of BPH was suggested caused by bacterial endosymbionts and yeasts that involved in insect nutrition. A wide range of endosymbionts had been associated with feeding capacity in BPH (Ferrater et al, 2015;Horgan et al, 2019). Resistant variety management is necessary and important to perform for extending effectiveness of the released varieties in the field (Horgan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation capability of BPH was suggested caused by bacterial endosymbionts and yeasts that involved in insect nutrition. A wide range of endosymbionts had been associated with feeding capacity in BPH (Ferrater et al, 2015;Horgan et al, 2019). Resistant variety management is necessary and important to perform for extending effectiveness of the released varieties in the field (Horgan, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, results from studies that examined differences in bacterial sysmbionts from the same virulent and avirulent planthopper populations have given inconsistent results (Tang et al, 2010; Wang et al, 2015; Xu et al, 2015). More recently, a study with green leafhoppers, Nephotettix virescens , has indicated consistent relations between abundance of the obligate symbiont Candida sulcus and virulence patterns following artificial selection (Horgan et al, 2019). A potential for endosymbiotic bacteria to determine planthopper virulence is noteworthy because of the role of bacteria in adaptation by insect herbivores to insecticidal proteins (Dowd and Shen, 1990; Dowd, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, considerable research attention has focused on the role of endosymbiotic microorganisms in virulence adaptation (Douglas, 1998, 2009; Noda et al, 2012; Ferrater et al, 2013; Hansen and Moran, 2014; Horgan et al, 2019). A number of studies have found that the densities of YLS in planthoppers vary depending on the nature of the plant host (vis-a-vis resistant or susceptible) and that densities change during selection for virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the results of our experiments demonstrate that virulence adaptation can be partial because it involves several virulence mechanisms, it involves both the male and the female parent, and likely involves both the planthopper and its mutualist symbionts. Partial resistance is most pronounced during virulence adaptation in leafhoppers—for example, adaptations for leafhopper ( Nephotettix virescens (Distant)) nymphs to feed and develop on resistant rice can take as little as 5 generations, but adaptations to lay eggs on resistant varieties can take a further 10–15 generations of selection [ 45 ]. Our planthoppers also demonstrated partial adaptation to IR62 (they survived and developed well but were inefficient feeders and had slow population growth).…”
Section: Discussionmentioning
confidence: 99%